2006
DOI: 10.1111/j.0735-2751.2006.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Desire in the Daydream Machine

Abstract: This article analyzes the sociality of illegal file sharing as one domain of teletechnology, using poststructural theory to conceptualize the file-sharing setting. It reveals the assumptions about file sharing in popular media, and demonstrates how the persistence of illegal file sharing across racial, economic, and status lines might be attributed to psychological and neurophysiological causes. To conclude, I consider the implications of poststructuralism for extension and synthesis in future social theory.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our ability to detail six structural elements used by the Freecycle online community enhances the literature's understanding of online sharing. Our structural assessment is distinct from previous forms of sharing research that have examined the open-source software projects that offer evidence of individuals sharing their time and effort (Hemetsberger, 2002(Hemetsberger, , 2006Lakhani & von Hippel, 2002;Stewart, 2005), the use of the Internet in sharing music and movies (Doane, 2006;Giesler, 2006), sharing themselves (Schau & Gilly, 2003), and even sharing experiences ranging from online gaming (Waskul & Lust, 2004) to sexual behavior (Merkle & Richardson, 2000), as well as research on virtual communities (Chan & Li, 2010;Wu, Chen, & Chung, 2010). Our assessment adds to the critical perspective of positive marketing (Mittelstaedt et al, 2015), in that it examines the structural aspects required to distribute repurposed goods within an online community.…”
Section: Contribution To Theorymentioning
confidence: 99%
“…Our ability to detail six structural elements used by the Freecycle online community enhances the literature's understanding of online sharing. Our structural assessment is distinct from previous forms of sharing research that have examined the open-source software projects that offer evidence of individuals sharing their time and effort (Hemetsberger, 2002(Hemetsberger, , 2006Lakhani & von Hippel, 2002;Stewart, 2005), the use of the Internet in sharing music and movies (Doane, 2006;Giesler, 2006), sharing themselves (Schau & Gilly, 2003), and even sharing experiences ranging from online gaming (Waskul & Lust, 2004) to sexual behavior (Merkle & Richardson, 2000), as well as research on virtual communities (Chan & Li, 2010;Wu, Chen, & Chung, 2010). Our assessment adds to the critical perspective of positive marketing (Mittelstaedt et al, 2015), in that it examines the structural aspects required to distribute repurposed goods within an online community.…”
Section: Contribution To Theorymentioning
confidence: 99%
“…Chiou, Huang, and Lee (2005) reported that attributive satisfaction, perceived prosecution risk, magnitude of consequence, and social consensus were important in influencing attitudes and behaviours toward illegal music downloading. Doane (2006) reported that household income and educational attainment were both negatively correlated with illegal music downloading. Cronan and Al-Rafee (2007) reported that attitude, past piracy behaviour, and moral obligation were major influences on why individuals pirated music.…”
Section: Introductionmentioning
confidence: 99%